AKUNTANSI QARDH - Khaidir Khaidir (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2015)
In addition, based on the Qur'an and the Hadith, the consensus of Islamic scholarshave also agreed that qardh can do. The agreement is based on human naturescholar who can not live without the help and support of his brother. No one haseverything that he needs. Therefore, borrowing has become a part of life in thisworld. And Islam is a religion that is concerned about all the needs of hiscommunity.